Bevacizumab Combined With Oxaliplatin/Capecitabine in Patient With Refractory and Recurrent Mucinous Adenocarcinoma of the Appendix: A Case Report - Liu, Wenzhi; Liu, Lili; Wang, Ruoyu; Gong, Guanyu; Ding, Xinjia; Yang, Bin; Bao, Yun; Wang, Zhiqiang; Zhang, Bo; Zhao, Dewei; Wu, Fei; Ding, Yan (Frontiers in Oncology, 2019)
Primary appendiceal adenocarcinoma with peritoneal pseudomyxoma has a high recurrence rate and refractory to medical interventions such as repetitive debulking surgery and systemic chemotherapy. Genome-based targeted therapy for such cases has not been well documented. Here we present a 63-year-old women, who was diagnosed with recurrent mucinous adenocarcinoma of the appendix with local invasions and peritoneal carcionmatosis, was refractory to systemic chemotherapy after surgery. We used a regime developed using whole exome sequencing. Somatic mutations in the genes encoding VEGFR2, FGFR1, FGFR2, FGFR3 and KRAS were identified in the patient’s tumor tissue. The patient was then treated with bevacizumab plus oxaliplatin. After four months of treatment, pelvic CT showed dramatic reduction of pseudomyoma and a decline of CA199 level from 5436.7U/ml to 1121.4U/ml. Continual treatment with bevacizumab-capecitabine remained effective and the patient’s CA199 level further decreased to 401.26U/ml according to the follow-up examination on Aug 15th, 2018. Results from this study show the evidence of gene mutations involving VEGF signal activation in the recurrence of appendiceal adenocarcinoma. Our results also suggest the association of these mutations with the effectiveness of anti-VEGF treatment using bevacizumab. Therefore, the screening of gene mutations involved in VEGF signaling and targeted therapy with anti-VEGF drugs may provide a new option to manage refractory/recurrent advanced-stage appendiceal adenocarcinoma.